2016
DOI: 10.1097/cin.0000000000000231
|View full text |Cite
|
Sign up to set email alerts
|

Health Worker mHealth Utilization

Abstract: This systematic review describes mHealth interventions directed at healthcare workers in low resource settings from the PubMed database from March, 2009 to May, 2015. Thirty-one articles were selected for final review. Four categories emerged from the reviewed articles: data collection during patient visits; communication between health workers and patients; communication between health workers; and public health surveillance. Most studies used a combination of quantitative and qualitative methods to assess ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
108
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(116 citation statements)
references
References 35 publications
4
108
1
3
Order By: Relevance
“…However, two systematic reviews on health professionals' acceptance found divergent results [25,26]. White et al concluded that health care professionals acceptance of using mHealth was generally very high [25]. Whereas, the other systematic review on health professionals' acceptance of mHealth varied in other studies [26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, two systematic reviews on health professionals' acceptance found divergent results [25,26]. White et al concluded that health care professionals acceptance of using mHealth was generally very high [25]. Whereas, the other systematic review on health professionals' acceptance of mHealth varied in other studies [26].…”
Section: Introductionmentioning
confidence: 99%
“…There is increasing evidence that mHealth interventions help patients to control their blood sugar levels [21][22][23] and elicit patient engagement [24]. However, two systematic reviews on health professionals' acceptance found divergent results [25,26]. White et al concluded that health care professionals acceptance of using mHealth was generally very high [25].…”
Section: Introductionmentioning
confidence: 99%
“…Observing the growth of the mobile phone in various communities around the world, many medical and public health scholars see mHealth as potentially impactful in the delivery of healthcare services, especially in communities that face significant challenges accessing healthcare services for a myriad of reasons that will be discussed further in this chapter (e.g., Malvey & Slovensky, 2014;Olla & Shimskey, 2015;Post et al, 2013;White, Thomas, Ezeanochie & Bull, 2016). Malvey and Slovensky (2014) view mHealth as having an emancipatory potential in terms of the delivery of healthcare services for hard-to-reach communities around the globe, opining that current research has indicated that there has already been good consensus among patients and community health workers regarding the desire for provision of healthcare services through mHealth avenues (e.g., Chang et al, 2013;Nachega et al, 2016).…”
Section: Mhealth and Communitymentioning
confidence: 99%
“…Studies consistently indicate that mHealth has the potential to increase patient compliance if community health workers acquired and adopted mHealth technologies positively to better communicate with patients. However, sustainability issues of these technologies are still a challenge (White et al, 2016). Katz, Mesfin, and Barr (2012) found that mHealth was useful in the management of chronic disease among low-income patients.…”
Section: Mhealth and Communitymentioning
confidence: 99%
See 1 more Smart Citation